Establishing APEX University:“Business as unusual” An interview with Professor Emeritus Dato’ Dr. Mohamad Zawawi Ismail, APEX University selection commitee chairman. - Shuib, Munir (National Higher Education Research Institute, Universiti Sains Malaysia, 2008)
For Higher Education in Malaysia September 2008 would be best remembered for the announcement of the first APEX University. So much anticipation, so much drama and so much suspense as everybody eagerly waited for the announcement by the Ministry of Higher Education (MoHE).